Mali : Technical Assistance Report: Continued Modernization of the Malian Tax System and Administration-Memorandum on Natural Resource Management. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Assistance Report discusses continued modernization of the Malian tax system and administration of natural resources. The Malian mining sector essentially consists of gold mining. The diversification policy is a failure at this point. The authorities' stated objective of diversifying mining production has not produced a clear, consistent action plan. Apart from precious substances, the high cost of bulk transportation (minerals), the technical and financial difficulties of local processing, and the weak domestic market make it unlikely that Mali's mining future can be defined other than by gold in the short or medium term.